Prevalence of autism spectrum disorder in a large, diverse metropolitan area: Variation by sociodemographic factors. Issue 1 (21st October 2021) - Shenouda, Josephine; Barrett, Emily; Davidow, Amy L.; Halperin, William; Silenzio, Vincent M. B.; Zahorodny, Walter
Abstract: Autism spectrum disorder (ASD) prevalence estimates have varied by region. In this study, ASD prevalence, based on active case finding from multiple sources, was determined at the county and school district levels in the New Jersey metropolitan area. Among children born in 2008, residing in a four‐county area and enrolled in public school in 2016, ASD prevalence was estimated to be 36 per 1000, but was significantly higher in one region—54 per 1000 and greater than 70 per 1000, in multiple school districts. Significant variation in ASD prevalence by race/ethnicity, socioeconomic status (SES), and school district size was identified. Highest prevalence was in mid‐SES communities, contrary to expectation. Prevalence among Hispanic children was lower than expected, indicating a disparity in identification. Comprehensive surveillance should provide estimates at the county and town levels to appreciate ASD trends, identify disparities in detection or treatment, and explore factors influencing change in prevalence. Lay Summary: We found autism prevalence to be 3.6% in New Jersey overall, but higher in one region (5.4%) and in multiple areas approaching 7.0%. We identified significant variation in autism spectrum disorder (ASD) prevalence by race/ethnicity, socioeconomic status (SES) and school district size. Mapping prevalence in smaller, well‐specified, regions may be useful to better understand the true scope of ASD, disparities in ASD detection and the factors impacting ASD prevalence estimation.